(untitled) (Baghdad Science Journal, 2009)
This study was conducted on five kinds of local soybean seeds (Ibaa, Hawija, Taqa.2, Lee74 and Hassan). The chemical analysis results showed that Hawija soybean has the highest percent of protein which was 38-08%, The amino acid percent was also higher than the other kinds(lysine, Thereonine and Tryptopham), and being 389,250,81 mg/gm nitrogen respectively Both amino acids were important for child nutrition. Hawija was selected, being the best for proteins and basic amino acids, and was utilized in preparation of the adjunct baby food formula. Eighteen formulas had been prepared by using soybean flour kind(Hawija), wheat flour kind (Abu gharib) and full fat powder milk (NIDO). Each formula contained 20% protein as recommended by F.A.O, W.H.O and Iraqi standard. The chemical analysis results showed that formulas had low moisture content(3.18-3.60%) and high carbohydrate content (59.10-60.12%), The protein and fat content was 19.23-20.81 and 14-4.35% respectively. The content of ash of the formulas were(2.50-3.23%),the calorie value was 430.17-432.42 K.cal /100 gm sample.the sensory evaluation showed that, the formulas with high contain in whole cream powder of milk or wheat flour, obtained higher sensory evaluation grades.